"It's About the Idea Hitting the Bull's Eye": How Aid Effectiveness Can Catalyse the Scale-up of Health Innovations - Deepthi Wickremasinghe; Meenakshi Gautham; Nasir Umar; Della Berhanu; Joanna Schellenberg; Neil Spicer (Kerman University of Medical Sciences, 2018)
Background Since the global economic crisis, a harsher economic climate and global commitments to address the problems of global health and poverty have led to increased donor interest to fund effective health innovations that offer value for money. Simultaneously, further aid effectiveness is being sought through encouraging governments in low- and middle-income countries (LMICs) to strengthen their capacity to be self-supporting, rather than donor reliant. In practice, this often means donors fund pilot innovations for three to five years to demonstrate effectiveness and then advocate to the national government to adopt them for scale-up within country-wide health systems. We aim to connect the literature on scaling-up health innovations in LMICs with six key principles of aid effectiveness: country ownership; alignment; harmonisation; transparency and accountability; predictability; and civil society engagement and participation, based on our analysis of interviewees' accounts of scale-up in such settings. Methods We analysed 150 semi-structured qualitative interviews, to explore the factors catalysing and inhibiting the scale-up of maternal and newborn health (MNH) innovations in Ethiopia, northeast Nigeria and the State of Uttar Pradesh, India and identified links with the aid effectiveness principles. Our interviewees were purposively selected for their knowledge of scale-up in these settings, and represented a range of constituencies. We conducted a systematic analysis of the expanded field notes, using a framework approach to code a priori themes and identify emerging themes in NVivo 10. Results Our analysis revealed that actions by donors, implementers and recipient governments to promote the scale-up of innovations strongly reflected many of the aid effectiveness principles embraced by well-known international agreements - including the Paris Declaration of Aid Effectiveness. Our findings show variations in the extent to which these six principles have been adopted in what are three diverse geographical settings, raising important implications for scaling health innovations in low- and middle-income countries. Conclusion Our findings suggest that if donors, implementers and recipient governments were better able to put these principles into practice, the prospects for scaling externally funded health innovations as part of country health policies and programmes would be enhanced.